情欲与贞节的纠葛 ： 探析“三言”中荡妇形象 = Disputation of lust and chastity : a study of slut Image in "San Yan" - 李婉怡 Lee, Wan Yi (2015)
“三言”作为话本小说的翘楚，涉及了不少以两性关系为题材的男女婚恋故事 。当中所塑造的女性形象并非单一的群体，而是被分化为多种类型。荡妇是其中之一。荡妇指的是行为放荡淫乱的妇人，这一类女性多在婚后红杏出墙。明代理学的兴盛 使得妇女的节操成为世人极为重视的问题，因此荡妇作为被社会边缘化的女性群体，“三言”对于其形象的建构寄寓着多重意义。本文首先将梳理明代与冯梦龙的性别观，以“三言”的荡妇形象为研究对象，从故事中荡妇红杏出墙的原因与结局来探 讨她们和情欲及贞节之间的关系。本文以文本细读的方式来分析荡妇形象及其贞节的发展，发现荡妇形象有着反映传统贞节观的淡薄、体现古代女性的社会地位与自我意识觉醒等的建构意义。As the pioneer of novel, “San Yan” has covered a lot of love stories revolving around the topic of gender relationship. The images of female characters shaped are not the same, instead they are differentiated into many types. Slut is one of them. Sluts refer to those women who behave promiscuously. Most of them are having an affair after marriage. The rise of Science (Li Xue) at the end of Ming Dynasty had made the behavior of woman became one of the main topic that the public paid much attention to. And sluts, as a group of women being isolated by the society, “San Yan” has given a lot of meaning and multiple metaphors to the image of sluts. This thesis first synthesizes the gender perspective of Ming Dynasty and Feng Meng Long by taking the slut image described in “San Yan” as research material, to investigate the women and their relations between lust and virginity from the reasons and consequences of them having an affair after marriage in the stories. This thesis takes close reading as an approach to analyse the image of sluts and the development of chastity to discover the image of sluts as a way to reflect the weak chastity consciousness in tradition, showing constructive meaning of the women status and the awakening of their self-consciousness in ancient time.